3D surface topography analysis in 5-axis ball-end milling. Issue 1 (2017) - Layegh K, S. Ehsan; Lazoglu, Ismail
Abstract: This article presents a new analytical model to predict the topography and roughness of the machined surface in 5-axis ball-end milling operation for the first time. The model is able to predict the surface topography and profile roughness parameters such as 3D average roughness (Sa) and 3D root mean square roughness (Sq) by considering the process parameters such as the feedrate, number of flutes, step-over and depth of cut as well as the effects of eccentricity and tool runout in 5-axis ball-end milling. This model allows to simulate the effects of the lead and tilt angles on the machined surface quality in the virtual environment prior to the costly 5-axis machining operations. The effectiveness of the introduced surface topography prediction model is validated experimentally by conducting 5-axis ball-end milling tests in various cutting conditions.